THE INFLUENCE OF INTELLECTUAL INTELLIGENCE AND EMOTIONAL INTELLIGENCE ON FIQIH ACHIEVEMENT AT MIM RANDUALAS - Meti Fatimah; Nashihun; Subando, Joko (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to examine the influence of intellectual intelligence and emotional intelligence on students' learning achievement of jurisprudence. The subjects of this study were 24 students at MIM Randualas Simo in 2023. Measurements were made using the adaptation scale of the FMS (Faith Maturity Scale) and DIT-2 (Defining Issues Test-2) and analyzed using the T test with the help of SPSS 16.00 for Windows. The results of the study show that the effect of intellectual intelligence on the learning achievement of Fiqh students of MIM Randualas Boyolali for the 2022/2023 academic year is significant 0.25. It means that if intellectual intelligence increases by 25% then Fiqh learning achievement also increases positively. Second, the Effect of Emotional Intelligence on Faith in Learning Achievement in Jurisprudence of MIM Randualas Boyolali Students for the 2022/2023 Academic Year is significant 0.22 and positive. It means that if Emotional Intelligence increases by 22% then Fiqh Learning Achievement increases positively. Third, the effect of intellectual intelligence and emotional intelligence jointly on achievement in learning Fiqh of MIM Randualas Boyolali students for the 2022/2023 academic year is significant and positive by 41.2%. This means that if intellectual intelligence and emotional intelligence together increase, the learning achievement of Fiqh also increases.